IDENTIFIKASI MISKONSEPSI PESERTA DIDIK MENGGUNAKAN THREE TIER DIAGNOSTIC TEST DALAM MATERI MATRIKS - Dian Safira; Yulis Jamiah; Hamdani Hamdani (UNIVERSITAS TANJUNGPURA, 2022)
This study aims to identify students' misconceptions and their causal factors using a three-tier diagnostic test in the matrix material at XI MAN 1 Pontianak. The research method used is descriptive method with a qualitative approach. The form of the research method in this research is a case study. The subjects of this study were 15 students of class XI MIPA 1 MAN 1 Pontianak. The research instrument used was a three-tier diagnostic test and interview guidelines. Based on the results of the study obtained by students who experienced calculation misconceptions as many as 1 student or 2,94% of 34 students, generalizing misconceptions experienced by 7 students or 20.59% of 34 students, misconceptions specialization experienced by 10 students or 29.41% of 34 students and misconceptions experienced by 1 student or 2.94% of 34 students. The causes of misconceptions experienced by students in this study came from wrong intuition and incomplete reasoning.